Contemporary art of Cusco: the second round - Tyuleneva, Vera (2011)
In July 2013 I published the article "Cusco: art and surroundings" (Tyuleneva 2013) in the electronic magazine Valicha. Its purpose was, neither more nor less, than to outline the panorama of Cusco art in recent years. Shortly after the article appeared, comments began to pour in. They were mostly embarrassed reactions from the artists: "Why am I not in your article?" It must be recognized that almost all the claims were fair and that my usual answers were reduced to "...because you don't fit into the mainstream", "...because I don't know how to classify you" or simply "...because I missed it". Almost immediately it became clear that the text was in need of revision and that the grievous omissions had to be rectified. This article is a new version of the same topic, expanded and corrected, but by no means definitive.